Case-Based Learning: Upaya Menstimulasi Intensi Remaja untuk Berkomunikasi Secara Adekuat dengan Orang Tua tentang Kesehatan Seksual - Riris Andriati; Lukman Handoyo; Lilis Minarsih (LPPM STIKES Guna Bangsa Yogyakarta, 2021)
Establishing communication about sexual health between parents and adolescents is a vital aspect of the family process. However, talking about sexual health are often considered taboo which discourages adolescents from discussing sexual health problems with their parents. The purpose of this community service was to stimulate the intention of adolescents to communicate adequately with their parents about their teenage lives, especially about sexual health. The case-based learning was conducted by applied the brain-storming discussion. The case-based learning method allows the team to present various cases from online media news about adolescent sexual health issues. Based on these cases, adolescent opinions about major impacts that would occur and what solutions were needed to prevent them were explored. The results show: (1) there was the emergence of intention, from the previous 70% of adolescents never had the intention or thought to tell their parents about their love life to 90% of adolescents agreed to slowly intend to be more open to their parents; and (2) there was the emergence of intention, from 60% of adolescents never having the intention or thought to tell their parents about sexual / reproductive health problems to 90% of adolescents agreeing to slowly intend to be more open to their parents. From these community service activities, it can be concluded that case-based learning activities are able to stimulate the adolescent intentions to communicate with parents about sexual health. It is highly recommended that this community service activity be continued by targeting the parents.